Molecular diagnosis using multi drug delivery network and stability - Jalil, M. A.; Innate, K.; Suwanpayak, N.; Yupapin, P. P.; Ali, J. (My University, 2011)
By using a pair of tweezers to generate the intense optical vortices within the PANDA ring resonator, the required molecules (drug volumes) can be trapped and moved dynamically within the molecular bus networks, in which the required diagnosis or drug delivery targets can be performed within the network. The advantage of the proposed system is that the proposed diagnostic method can perform within the tiny system (thin film device or circuit), which can be available for a human embedded device for diagnostic use. The channel spacing of the trapped volumes (molecules) within the bus molecular networks can be provided. © 2011 Informa Healthcare USA, Inc.
Keywords: drug delivery networks; molecular diagnosis; molecular networks; neural system and network